The Pink-headed Duck - Ali, Slim (Wildfowl, 1960)
For the last ten years or so there has been continuing effort on the part of the Bombay Natural History Society through its widespread membership in India and sportsmen in general to re-discover the Pink-headed Duck, or at least to obtain some dependable clues concerning its present status. The recorded history of the Pink-headed Duck, such as it is, is well known and no new information has emerged within recent years. Since it was first described in 1790 the species has at no time been recorded as common anywhere.